2023
DOI: 10.1111/all.15757
|View full text |Cite
|
Sign up to set email alerts
|

The future of food allergy: Challenging existing paradigms of clinical practice

Abstract: The field of food allergy has seen tremendous change over the past 5–10 years with seminal studies redefining our approach to prevention and management and novel testing modalities in the horizon. Early introduction of allergenic foods is now recommended, challenging the previous paradigm of restrictive avoidance. The management of food allergy has shifted from a passive avoidance approach to active interventions that aim to provide protection from accidental exposures, decrease allergic reaction severity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 205 publications
0
4
0
Order By: Relevance
“…This selective participation could have led to an overestimation of the overall lifetime prevalence of self-reported SAR to bee venom, particularly for mild grades (grade I: 233 out of 852 (27.3%); grade II: 111 out of 852 (13.0%)) ( 20 ). The phenomenon of overestimation in both parental and self-reported data is a well-documented issue in assessing the prevalence of food allergies ( 29 ), and has also been reported in the context of HVA. Studies conducted in Poland revealed an overestimation in the prevalence of LLR and mild SAR when comparing self-reported estimates to those objectively assessed by a physician ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…This selective participation could have led to an overestimation of the overall lifetime prevalence of self-reported SAR to bee venom, particularly for mild grades (grade I: 233 out of 852 (27.3%); grade II: 111 out of 852 (13.0%)) ( 20 ). The phenomenon of overestimation in both parental and self-reported data is a well-documented issue in assessing the prevalence of food allergies ( 29 ), and has also been reported in the context of HVA. Studies conducted in Poland revealed an overestimation in the prevalence of LLR and mild SAR when comparing self-reported estimates to those objectively assessed by a physician ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is an additional challenge in some patients with severe allergies not qualifying for OFCs due to the substantial risk of severe allergic reactions. Therefore, a critical aspect of the current landscape is the need to explore alternative diagnostic methods that can alleviate these challenges 20–22 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a critical aspect of the current landscape is the need to explore alternative diagnostic methods that can alleviate these challenges. [20][21][22] In this context, researchers have turned to BATs and MATs as potential solutions. These in vitro tests, in theory, offer numerous advantages over OFCs.…”
Section: Subgroup Analysis: Sensitized or Allergicmentioning
confidence: 99%
“…Foods such as eggs, milk, soybeans, and peanuts are commonly identified as primary triggers. By avoiding or limiting these foods, the incidence of allergies can potentially be reduced [ 5 ]. However, improper dietary restrictions, such as not providing suitable alternative foods, can lead to malnutrition and hinder growth in rapidly developing infants and young children.…”
Section: Introductionmentioning
confidence: 99%